Intestinal obstruction caused by malrotation of the gut in atrial isomerism. Issue 11 (November 1989) - Sharland, M R; Chowcat, N L; Qureshi, S A; Drake, D P
Abstract : Five children with atrial isomerism developed intestinal obstruction caused by malrotation of the gut. Other than asplenia, the extracardiac anomalies in these syndromes are rarely regarded as important as the outcome after intestinal surgery is poor. As cardiac treatment improves, early investigation and intervention for intestinal symptoms becomes more important.